The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.20344/amp.8976
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Postembolization Syndrome after Transarterial Chemoembolization for Hepatocellular Carcinoma Treatment

Abstract: RESUMOIntrodução: A quimioembolização hepática é uma técnica amplamente usada para o tratamento do carcinoma hepatocelular. A principal complicação deste procedimento é a síndrome pós-quimioembolização. O principal objetivo deste estudo foi determinar fatores de risco para síndrome pós-quimioembolização. Material e Métodos: Análise retrospetiva unicêntrica de 563 procedimentos de quimioembolização hepática efetuados entre 1/1/2014-31/12/2015. A quimioembolização hepática foi efetuada com ½ -2 ampolas de microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…No sources of data on blood vessel invasion as a risk factor for pain were found when conducting a literature review; thus, our study is the first in this respect, identifying blood vessel invasion as a predictor of pain. Tumor invasion of the portal vein is more common in the late stages of cancer[ 17 ], and is often accompanied by tumors that are large in size and/or numerous, which may be attributable to tumor necrosis and a more marked inflammatory response, which is caused by embolization of a larger site[ 18 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…No sources of data on blood vessel invasion as a risk factor for pain were found when conducting a literature review; thus, our study is the first in this respect, identifying blood vessel invasion as a predictor of pain. Tumor invasion of the portal vein is more common in the late stages of cancer[ 17 ], and is often accompanied by tumors that are large in size and/or numerous, which may be attributable to tumor necrosis and a more marked inflammatory response, which is caused by embolization of a larger site[ 18 - 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study reported that elderly patients may have less pain after TACE than young patients, 13 whether age can influence post-TACE pain is rather controversial. 14,28 Thus, further prospective studies should be conducted to confirm this finding. Furthermore, the multivariate analysis in the present study using the CART algorithm showed similar risk factors and supported the findings from the ordinal logistic regression analysis.…”
Section: Discussionmentioning
confidence: 82%
“…This complication is particularly common with a sufficient embolus, and it is caused by tumor necrosis ( 14 ). Major symptoms include fever, elevated ALT and aspartate transaminase levels, nausea, vomiting, and abdominal pain, though most cases resolve within a few days of symptom onset and with symptomatic treatment if necessary ( 15 ).…”
Section: Discussionmentioning
confidence: 99%